plicación de la metodología RUP (Rational Unified Process) para el desarrollo de un sistema de control de pacientes, hospitalización y de facturación para la clínica de la mujer y el niño en la ciudad de Babahoyo. - Carbo Villavicencio, Katiusca (2015)
Application of the methodology RUP (Rational Unified Process) for the development of a control system of patient, hospitalization and of billing for the woman's clinic and the boy in the city of Babahoyo. In this thesis work a control system has been developed of patient, hospitalization and billing for the woman's clinic and the boy. With this software one can obtain a control of all the patients that you/they attend the clinic in an easy and quick way. The computer software has been developed using the following tools: • Visual Microsoft Studio.Net 2010. • Database SQL Server 2005. For the development of the system computer use the engineering of the software which was implanted by the methodology RUP that has four phases that are: • Beginning • Elaboration • Construction • Transition 11